Photocurable coating composition and coated article

By using specific organopolysiloxane, ultraviolet absorber and photopolymerization initiator in the photocurable coating composition, the problem of difficult to maintain weather resistance, water resistance and stain resistance during outdoor use is solved, and excellent abrasion resistance and long-term stability of the coating film are achieved.

CN119894995APending Publication Date: 2025-04-25SHIN ETSU CHEMICAL CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202380065228.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-12
Filing Date
2023-07-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The conventional photocurable (meth)acrylic coating composition is difficult to maintain weather resistance, water resistance and stain resistance when used outdoors.

Method used

The photocurable coating composition containing a specific organopolysiloxane, an ultraviolet absorber and a photopolymerization initiator is used to ensure that the content of the component (A) is between 30 and 99 mass%, and the ultraviolet absorber with a (meth)acryloyl group and silica particles modified with alkoxysilane surface are used.

Benefits of technology

It forms a coating with excellent abrasion resistance, waterproofness and stain resistance, and maintains these characteristics after weather resistance tests, which is suitable for outdoor long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894995A_ABST
    Figure CN119894995A_ABST
Patent Text Reader

Abstract

A photocurable coating composition containing (A) an organopolysiloxane represented by formula (1) (R1 each independently represents a hydrogen atom or a monovalent hydrocarbon group into which an oxygen atom or the like may be interposed, X each independently represents a divalent saturated hydrocarbon group into which an oxygen atom or the like may be interposed, Q each independently represents a (a + 1)-valent saturated hydrocarbon group into which an oxygen atom or the like may be interposed, and X each independently represents a hydrogen atom or the like. P independently represents an acryloyloxy group or a methacryloyloxy group, a independently represents an integer of 2-5, and n represents an integer of 0-100. ), (B) an ultraviolet light absorber, and (C) a photopolymerization initiator, the content of component (A) being 30-99 mass% in terms of non-volatile components, the photocurable coating composition being capable of forming a coating film that exhibits excellent scratch resistance, water repellency, and antifouling properties and maintains these properties even when used outdoors for a long period of time. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to photocurable coating compositions and coated articles. Background Art

[0002] In recent years, as protective coating agents for the surfaces of various substrates such as various plastics (polycarbonate, polymethyl methacrylate, polystyrene, polyester, polyolefin, epoxy resin, melamine resin, triacetyl cellulose resin, ABS resin, AS resin, norbornene resin, etc.), metals, and wood, there has been a demand for curable compositions that have excellent coating properties, appearance, transparency, scratch resistance, surface slip, low curling, adhesion, and chemical resistance, and that can form a cured film with excellent weather resistance.

[0003] In addition, it is desired that the above-mentioned properties be satisfied by a photocurable composition that can be cured in a short time with relatively low energy, compared with a thermosetting composition that takes a relatively long time to cure and requires a large amount of energy.

[0004] As a general photocurable coating composition, a photocurable (meth)acrylic composition using a multifunctional (meth)acrylate is well known. The photocurable (meth)acrylic composition comprises one or more multifunctional (meth)acrylates and a photopolymerization initiator, and forms a coating film by crosslinking through photopolymerization of the (meth)acryloyl group in the multifunctional (meth)acrylate, thereby exhibiting excellent curability, scratch resistance, hardness, and chemical resistance.

[0005] By mixing a fluorine-based additive having a perfluoropolyether group and a (meth)acryloyl group as a water-repellent and antifouling group into these photocurable (meth)acrylic coating compositions, a coating having water-repellent and antifouling properties in addition to the above-mentioned properties can be obtained (Patent Documents 1 to 3). In addition, as a fluorine-based additive, a compound in which a cyclic polysiloxane is linked by a divalent perfluoropolyether chain is also known (Patent Document 4).

[0006] Furthermore, curable compositions are known in which the sliding property and the erasability of fingerprints and oil-based dyes are improved by compounding a small amount of polysiloxane having a (meth)acryloyl group (Patent Documents 5 to 7).

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2007-145884

[0010] Patent Document 2: Japanese Patent Application Publication No. 2010-53114

[0011] Patent Document 3: Japanese Patent Application Publication No. 2010-138112

[0012] Patent Document 4: Japanese Patent Application Publication No. 2010-285501

[0013] Patent Document 5: Japanese Patent No. 4910253

[0014] Patent Document 6: Japanese Patent Application Publication No. 2005-036018

[0015] Patent Document 7: Japanese Patent Application Publication No. 2008-081575 Summary of the invention

[0016] Problems to be solved by the invention

[0017] On the other hand, photocurable (meth)acrylic coating compositions also have a problem of improving weather resistance, particularly in applications such as outdoor use.

[0018] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide a photocurable coating composition and a coated article which can form a coating film which exhibits excellent scratch resistance, water resistance and stain resistance and maintains these properties even when used outdoors for a long period of time.

[0019] Means for solving problems

[0020] The present inventors have conducted intensive studies to achieve the above-mentioned purpose and have found that a photocurable coating composition containing the following components (A) to (C) can form a coating having excellent scratch resistance, water resistance, and antifouling properties, and that these properties are maintained even after a weather resistance test, thereby completing the present invention.

[0021] That is, the present invention provides:

[0022] 1. A photocurable coating composition comprising:

[0023] (A) an organopolysiloxane represented by the following formula (1),

[0024] [Chemistry 1]

[0025]

[0026] (Where R 1 independently represent a hydrogen atom or a monovalent hydrocarbon group which may have an oxygen atom interposed therein,

[0027] X independently represents a divalent saturated hydrocarbon group which may contain one or more atoms selected from oxygen, nitrogen, sulfur and phosphorus atoms,

[0028] Q independently represents a (a+1)-valent saturated hydrocarbon group which may contain one or more atoms selected from oxygen, nitrogen, sulfur, phosphorus and silicon atoms,

[0029] P independently represents an acryloyloxy group or a methacryloyloxy group,

[0030] a independently represents an integer from 2 to 5,

[0031] n represents an integer from 0 to 100. )

[0032] (B) an ultraviolet absorber, and

[0033] (C) a photopolymerization initiator,

[0034] The content of component (A) calculated as a non-volatile component is 30 to 99% by mass;

[0035] 2. The photocurable coating composition according to 1, wherein the R 1 is methyl;

[0036] 3. The photocurable coating composition according to 1, wherein the Xs are independently divalent saturated hydrocarbon groups having 2 to 30 carbon atoms that may be interposed with oxygen atoms;

[0037] 4. The photocurable coating composition according to 3, wherein X is a group represented by the following formula (2);

[0038] [Chemistry 2]

[0039]

[0040] (In the formula, *1 is bonded to the silicon atom of the formula (1), and *2 is bonded to the oxygen atom in the urethane group of the formula (1).)

[0041] 5. The photocurable coating composition according to 1, wherein the Qs are independently saturated hydrocarbon groups having 4 to 30 carbon atoms and having a urethane bond and a valence of (a+1);

[0042] 6. The photocurable coating composition according to 1, wherein n is an integer of 1 to 80;

[0043] 7. The photocurable coating composition according to 1, wherein the component (B) is a UV absorber having a (meth)acryloyl group;

[0044] 8. The photocurable coating composition according to 1, comprising (D) one or more selected from an organopolysiloxane having a (meth)acryloyl group but not having a urethane bond, and silica particles surface-modified with an alkoxysilane having a (meth)acryloyl group but not having a urethane bond;

[0045] 9. The photocurable coating composition according to 1, comprising (E) a (meth)acrylate compound having no silicon atom (but excluding the component (B));

[0046] 10. A cured film of the photocurable coating composition according to any one of 1 to 9;

[0047] 11. A coated article comprising: a substrate, and a cured film of the photocurable coating composition according to 10 formed on the substrate directly or via at least one other layer;

[0048] 12. The coated article according to 11, wherein the substrate is an organic resin or wood.

[0049] Effects of the Invention

[0050] According to the present invention, it is possible to provide a photocurable coating composition which can form a coating film which exhibits excellent scratch resistance, water resistance, and antifouling properties and which maintains these properties even when used outdoors for a long period of time. DETAILED DESCRIPTION

[0051] The present invention will be described in detail below.

[0052] The photocurable coating composition of the present invention comprises (A) an organopolysiloxane having a plurality of (meth)acryloyl groups at both terminals via urethane bonds, (B) an ultraviolet absorber, and (C) a photopolymerization initiator.

[0053] [1](A)Ingredients

[0054] The component (A) is an organopolysiloxane represented by the following general formula (1).

[0055] [Chemistry 3]

[0056]

[0057] In formula (1), R 1 Each of the above groups independently represents a hydrogen atom or a monovalent hydrocarbon group into which an oxygen atom may be introduced, each of the above groups independently represents a divalent saturated hydrocarbon group into which one or more oxygen, nitrogen, sulfur and phosphorus atoms may be introduced, each of the above groups independently represents a (a+1)-valent saturated hydrocarbon group into which one or more oxygen, nitrogen, sulfur, phosphorus and silicon atoms may be introduced, each of the above groups independently represents an acryloyloxy group or a methacryloyloxy group, each of the above groups independently represents an integer from 2 to 5, and each of the above groups independently represents an integer from 0 to 100.

[0058] The above R 1 The monovalent hydrocarbon group may be linear, branched or cyclic, and is preferably a monovalent hydrocarbon group having 1 to 20 carbon atoms.

[0059] Specific examples thereof include alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-hexyl, cyclohexyl, n-octyl, 2-ethylhexyl, and n-decyl; alkenyl groups such as vinyl, allyl (2-propenyl), 1-propenyl, isopropenyl, and butenyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; and aralkyl groups such as benzyl, phenylethyl, and phenylpropyl.

[0060] Among these, R 1 , preferably a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 12 carbon atoms, more preferably an alkyl group having 1 to 10 carbon atoms, further preferably an alkyl group having 1 to 5 carbon atoms, and further preferably a methyl group.

[0061] Furthermore, the monovalent hydrocarbon group may have an oxygen atom inserted in the molecular chain or at the Si-side terminal, and may be, for example, an alkoxy group having 1 to 20 carbon atoms.

[0062] The divalent saturated hydrocarbon group in which at least one selected from oxygen, nitrogen, sulfur and phosphorus atoms may be inserted as X may be any of linear, branched and cyclic groups, but preferably is an alkylene group having 1 to 20 carbon atoms, an oxyalkylene group having 1 to 20 carbon atoms, or a polyoxyalkylene group having 1 to 20 carbon atoms. Among these, a group represented by the following formula (2) is more preferred in view of ease of synthesis, availability of raw materials and the like.

[0063] [Chemistry 4]

[0064]

[0065] (In the formula, *1 is bonded to the silicon atom of formula (1), and *2 is bonded to the oxygen atom in the urethane group of formula (1).)

[0066] Q may be a (a+1)-valent, preferably 3-6-valent saturated hydrocarbon group, which may be branched or cyclic, and may be one of at least one of oxygen, nitrogen, sulfur, phosphorus and silicon atoms. Examples thereof include -CH<, -CH2CH<, -CH(CH3)CH<, -C(CH3)(CH2-)2 and other branched trivalent saturated hydrocarbon groups having 1 to 10 carbon atoms; -(CH2)6-NHCO-OR 2 (-) c , -CH2CH(CH3)CH2C(CH3)2CH2CH2-NHCO-OR 2 (-) c , -CH2C(CH3)2CH2CH(CH3)CH2CH2-NHCO-OR 2 (-) c , -R 3 -NHCO-OR 2 (-) cA branched or cyclic trivalent to hexavalent saturated hydrocarbon group having 4 to 30 carbon atoms and containing a urethane bond. 2 The number of Ps to be bonded is an integer of 2-5.

[0067] The above R 2 Preferably, it is a branched or cyclic trivalent to hexavalent saturated hydrocarbon group which may have oxygen and nitrogen atoms. Specific examples thereof include -CH(CH2-)2, -CH2-C(CH2-)3, -(CH2CH2O) d -CH2C(CH2-)3, -(CH2CH2O) d -CH2C(CH2-(OCH2CH2) d -)3, -(CH2CH(CH3)O) d -CH2C(CH2-(OCH(CH3)CH2) d -)3, -CH2CH2-Z-(CH2CH2-)2, -CH2CH2-Z-(CH2CH2-)2, -CH2CH2-Z-(CH2CH2O-C(=O)(CH2)5-O-)2, -CH2-C(CH2-)2-CH2OCH2-C(CH2-)3 and the like. Among them, Z is an isocyanurate skeleton residue [*3-NC(=O)NC(=O)NC(=O)-*4], and *3 and *4 are bonded to each other to form a ring structure.

[0068] The above R 3 It is preferably a cyclic tri- to hexavalent saturated hydrocarbon group having 10 to 30 carbon atoms and in which an oxygen or nitrogen atom may be introduced, and more preferably a residue obtained by removing two isocyanate groups of isophorone diisocyanate.

[0069] Among these, in consideration of ease of synthesis, availability of raw materials, etc., Q is more preferably a group represented by the following formulae (3) to (12).

[0070] [Chemistry 5]

[0071]

[0072] [Chemistry 6]

[0073]

[0074] [Chemistry 7]

[0075]

[0076] [Chemistry 8]

[0077]

[0078] [Chemistry 9]

[0079]

[0080] [Chemistry 10]

[0081]

[0082] [Chemistry 11]

[0083]

[0084] [Chemistry 12]

[0085]

[0086] [Chemistry 13]

[0087]

[0088] [Chemistry 14]

[0089]

[0090] In formulae (3) to (12), *5 is bonded to P in formula (1), and *6 is bonded to the nitrogen atom in the urethane group in formula (1).

[0091] In formula (1), a represents the number of Ps bonded to Q and is an integer of 2 to 5, preferably an integer of 3 to 5. If a is less than 2, the curability of the composition and the scratch resistance of the resulting coating film may be insufficient, while if a exceeds 5, the crack resistance of the coating film may be poor.

[0092] n is an integer of 0 to 100, preferably an integer of 1 to 80, and more preferably an integer of 3 to 60. When n exceeds 100, coating properties may be deteriorated or poor appearance such as uneven coating may occur in the coating film.

[0093] The content of component (A) is in the range of 30 to 99% by mass, preferably 35 to 80% by mass, relative to the non-volatile components of the entire composition. If it is less than 30% by mass, the obtained cured coating film has poor water resistance and antifouling properties, and sometimes cannot fully exhibit weather resistance. If it exceeds 99% by mass, the adhesion between the obtained cured coating film and the substrate may be reduced.

[0094] [2] (B) Component

[0095] The component (B) is a UV absorber and is not particularly limited as long as it absorbs UV rays, and examples thereof include hydroxybenzophenones, hydroxybenzotriazoles, and hydroxyphenyltriazines.

[0096] Specific examples thereof include 2,4-dihydroxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxy-4-n-benzyloxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-diethoxybenzophenone, 2,2'-dihydroxy-4,4'-dipropoxybenzophenone, 2,2'-dihydroxy-4,4'-dibutoxybenzophenone, 2,2'-dihydroxy-4-methoxy-4'-propoxybenzophenone, 2,2'-dihydroxy-4-methoxy-4'-butoxybenzophenone, benzotriazole, 2-(2-hydroxy-5-tert-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-butylphenyl)benzotriazole, ethyl-2-cyano-3,3-diphenylacrylate, 2-ethylhexyl-2-cyano-3,3-diphenylacrylate, 2-(2-hydroxy-4-hexyloxyphenyl)-4,6-diphenyltriazine, 2-[4-[(2-hydroxy-3-(2'-ethyl)hexyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine), 2-[2-hydroxy-4-(1-octyloxycarbonylethoxy)phenyl]-4,6-bis(4-phenylphenyl)-1,3,5-triazine) and the like.

[0097] As the component (B), a UV absorber containing a (meth)acryloyloxy group is preferred. As long as such a UV absorber forms a crosslink with the above-mentioned component (A) and other (meth)acrylate compounds, it will not precipitate or fall off from the coating film after being introduced, thereby achieving long-term weather resistance.

[0098] Specific examples of the hydroxybenzophenone having a (meth)acryloyloxy group include 2-hydroxy-4-(2-(meth)acryloyloxyethoxy)benzophenone, 2-hydroxy-4-(4-(meth)acryloyloxybutoxy)benzophenone, 2,2'-dihydroxy-4-(2-(meth)acryloyloxyethoxy)benzophenone, 2,4-dihydroxy-4'-(2-(meth)acryloyloxyethoxy)benzophenone, 2,2',4-trihydroxy-4'-(2-(meth)acryloyloxyethoxy)benzophenone, 2-hydroxy-4-(3-(meth)acryloyloxy-2-hydroxypropoxy)benzophenone, and 2-hydroxy-4-(3-(meth)acryloyloxy-1-hydroxypropoxy)benzophenone.

[0099] Specific examples of the hydroxybenzotriazole having a (meth)acryloyloxy group include 2-(2'-hydroxy-5'-(meth)acryloyloxyphenyl)-2H-benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-(meth)acryloyloxymethylphenyl)-2H-benzotriazole, 2-[2'-hydroxy-5'-(2-(meth)acryloyloxyethyl)phenyl]-2H-benzotriazole, 2-[2'-hydroxy-3'-tert-butyl-5'-(2-(meth)acryloyloxyethyl)phenyl]-5-chloro-2H-benzotriazole, and 2-[2'-hydroxy-3'-methyl-5'-(8-(meth)acryloyloxyoctyl)phenyl]-2H-benzotriazole.

[0100] Specific examples of the hydroxyphenyl triazine having a (meth)acryloyloxy group include a reaction product of 2-[4-[(2-hydroxy-3-(2'-ethyl)hexyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine) and 2-acryloyloxyethyl isocyanate (e.g., Synthesis Example 1 of Japanese Patent No. 6354665), a reaction product of 2-[4-[(2-hydroxy-3-(2'-ethyl)hexyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine) and 1,1-bis(acryloyloxyethyl isocyanate, The invention also relates to a reaction product of 2-[4-{(hydroxy-3-dodecyloxypropyl)oxy}-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine) and 2-acryloyloxyethyl isocyanate, and a reaction product of 2-[4-{(hydroxy-3-dodecyloxypropyl)oxy}-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine) and 1,1-bis(acryloyloxymethyl)ethyl isocyanate.

[0101] These ultraviolet absorbers may be used in combination of two or more.

[0102] The content of the component (B) is preferably 10 to 30% by mass, more preferably 15 to 20% by mass, based on the nonvolatile content of the entire composition, from the viewpoint of weather resistance and coating film appearance.

[0103] [3] (C) Component

[0104] The photopolymerization initiator of the component (C) may be appropriately selected from the viewpoint of compatibility and curability in the coating composition, and specific examples thereof include benzoin, benzoin monomethyl ether, benzoin isopropyl ether, acetoin, benzil, benzophenone, p-methoxybenzophenone, diethoxyacetophenone, benzyl dimethyl ketal, 2,2-diethoxyacetophenone, 1-hydroxycyclohexyl phenyl ketone, methyl phenyl glyoxylate, 2-hydroxy-2-methyl-1-phenylpropane-1-one and the like. Sulfur compounds such as tetramethylthiuram monosulfide and tetramethylthiuram disulfide; phosphorus oxide compounds such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylethoxyphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide; 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone-1, camphorquinone, etc. These can be used alone or in combination of two or more, and can be combined arbitrarily according to the desired coating performance.

[0105] In order to obtain a proper curing speed of the obtained coating film, improve the scratch resistance and adhesion to the substrate of the cured coating film, and prevent coloration and reduced weather resistance, the content of component (C) is preferably 0.1 to 10% by mass, and more preferably 1 to 8% by mass, relative to the total amount of the non-volatile components in the composition.

[0106] [4] (D) Component

[0107] In order to improve the transparency, scratch resistance, substrate adhesion, durability, etc. of the coating film, the photocurable coating composition of the present invention may contain (D) one or more selected from an organopolysiloxane having a (meth)acryloyl group but not having a urethane bond, and silica particles surface-modified with an alkoxysilane having a (meth)acryloyl group but not having a urethane bond, as needed.

[0108] The organopolysiloxane having a (meth)acryloyl group but not having a urethane bond can be obtained, for example, by subjecting an alkoxysilane having a (meth)acryloyl group but not having a urethane bond, or a mixture thereof with other silanes to (co)hydrolysis condensation.

[0109] In addition, silica particles surface-modified with alkoxysilane having a (meth)acryloyl group but not having a urethane bond can be obtained by a method in which an alkoxysilane having a (meth)acryloyl group but not having a urethane bond, or a mixture thereof with other silanes, is (co)hydrolyzed and condensed in the presence of colloidal silica, or by a method in which silica powder is dry-treated with these alkoxysilanes.

[0110] Specific examples of alkoxysilanes having a (meth)acryloyl group but not having a urethane bond include 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 2-(meth)acryloxyethyltrimethoxysilane, 2-(meth)acryloxyethyltriethoxysilane, (meth)acryloxymethyltrimethoxysilane, (meth)acryloxymethyltriethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 8-(meth)acryloxyoctyltrimethoxysilane, and 8-(meth)acryloxyoctyltriethoxysilane.

[0111] As component (D), if considering the compatibility with other components, heat resistance, chemical resistance, durability, and excellent adhesion to the substrate, 3-(meth)acryloxypropyltrimethoxysilane alone or its (co)hydrolysis condensate with other silanes, or a product obtained by (co)hydrolysis condensation of 3-(meth)acryloxypropyltrimethoxysilane alone or with other silanes in the presence of colloidal silica is preferred. These may be used alone or in combination of two or more, and may be combined arbitrarily according to the desired coating performance.

[0112] Considering transparency, scratch resistance, substrate adhesion, durability, etc. of the coating film, the amount of component (D) when used is preferably 10 to 50% by mass, more preferably 20 to 40% by mass, based on the total amount of nonvolatile components in the composition.

[0113] [5] (E) Component

[0114] The photocurable coating composition of the present invention may contain (E) a (meth)acrylate compound having no silicon atom in addition to the above-mentioned (A), (B) and (D) components, if necessary, in order to improve the transparency, scratch resistance, substrate adhesion, durability, etc. of the coating film.

[0115] Examples of such (meth)acrylate compounds include one or more (meth)acrylates selected from monofunctional (meth)acrylates or polyfunctional (meth)acrylates, urethane (meth)acrylates, epoxy (meth)acrylates, polyester (meth)acrylates, etc. Among these, monofunctional and polyfunctional (meth)acrylates, and urethane (meth)acrylates are preferred from the viewpoints of productivity and durability.

[0116] Specific examples of the monofunctional (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, morpholinyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, glycidyl (meth)acrylate, dimethyl (meth)acrylate, (meth)acrylate compounds such as mono(meth)acrylates such as 2-ethoxyethyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, and phenyl (meth)acrylate, and an adduct of phthalic anhydride and 2-hydroxyethyl (meth)acrylate.

[0117] Specific examples of the multifunctional (meth)acrylate include neopentyl glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol (number of repeating units (hereinafter referred to as "k") = 2 to 15) di(meth)acrylate, polypropylene glycol (k = 2 to 15) di(meth)acrylate, polybutylene glycol (k = 2 to 15) di(meth)acrylate, 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, propane, trimethylolpropane diacrylate, bis(2-(meth)acryloyloxyethyl)-hydroxyethyl-isocyanurate, trimethylolpropane tri(meth)acrylate, tri(2-(meth)acryloyloxyethyl)isocyanurate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy di(meth)acrylate obtained by reacting bisphenol A type diepoxy with (meth)acrylic acid acrylate, urethane tri(meth)acrylate obtained by reacting a trimer of 2-hydroxyethyl(meth)acrylate and 1,6-hexamethylene diisocyanate, urethane di(meth)acrylate obtained by reacting isophorone diisocyanate and 2-hydroxypropyl(meth)acrylate, urethane hexa(meth)acrylate obtained by reacting isophorone diisocyanate and pentaerythritol tri(meth)acrylate, Urethane di(meth)acrylates obtained by reacting a urethanization reaction product of dicyclohexylmethane diisocyanate and poly(k=6-15)tetramethylene glycol with 2-hydroxyethyl(meth)acrylate, etc. urethane poly(meth)acrylates, polyester (meth)acrylates obtained by reacting trimethylolethane with succinic acid and (meth)acrylic acid, polyester poly(meth)acrylates such as polyester (meth)acrylates obtained by reacting trimethylolpropane with succinic acid, ethylene glycol and (meth)acrylic acid, etc.

[0118] Furthermore, other additives may be added to the photocurable coating composition of the present invention within a range not impairing the effects of the present invention.

[0119] Examples of such additives include antifouling agents, water repellents, leveling agents, colorants, pigments, antioxidants, anti-yellowing agents, bluing agents, defoaming agents, thickeners, anti-settling agents, antistatic agents, surfactants, adhesion promoters, infrared absorbers, light stabilizers, flexibility imparting agents, curing catalysts, metal oxide particles, and the like.

[0120] Furthermore, the photocurable coating composition of the present invention may contain an organic solvent, and the organic solvent is preferably selected and used according to the coating method.

[0121] For example, when used in spray coating, it is preferred to arbitrarily combine alcohol solvents such as isobutyl alcohol, glycol solvents such as propylene glycol monomethyl ether, ester solvents such as n-butyl acetate, ketone solvents such as methyl isobutyl ketone, and aromatic solvents such as toluene so that the viscosity of the coating composition is 20 mPa·s or less. When used in coating by spray flow coating or dip coating, it is preferred to make the viscosity of the coating composition 100 mPa·s or less.

[0122] In the case of a high-solid coating composition having a solid content exceeding 80% by mass, the solvent can be appropriately selected in consideration of the solubility of various additives.

[0123] The photocurable coating composition of the present invention is applied to various substrates and cured to form a cured coating film.

[0124] In photocuring, the coating composition is applied to the substrate to form a predetermined film thickness, and then, after the solvent is volatilized as needed, ultraviolet rays, electron beams, etc. are irradiated using a high-pressure mercury lamp, a metal halide lamp, an LED lamp, etc. The irradiation atmosphere may be in air or in an inert gas such as nitrogen or argon.

[0125] Examples of the substrate include organic resins such as plastic molded products, wood products, fibers, ceramics, glass, metals, and composites thereof, but are not particularly limited. The coating composition of the present invention can be suitably used for various plastic materials.

[0126] In particular, it can be suitably used for polycarbonate resins, polystyrene resins, acrylic resins, modified acrylic resins, polyurethane resins, thiourethane resins, condensates of halogenated bisphenol A and ethylene glycol, acrylic polyurethane resins, acrylic resins containing halogenated aromatic groups, sulfur-containing resins, polyalkylene terephthalate resins, cellulose resins, amorphous polyolefin resins, and composite resins thereof.

[0127] In addition, products in which the surfaces of these resin substrates have been treated, specifically, products in which chemical conversion treatment, corona discharge treatment, flame treatment, plasma treatment, acid solution treatment, or alkali solution treatment have been performed can also be used. In addition, laminates in which the surface layer is coated with a resin of a different type from that of the substrate body can be used.

[0128] Specific examples of the laminate include a laminate having an acrylic resin layer or a polyurethane resin layer on the surface of a polycarbonate resin substrate and a laminate having an acrylic resin layer on the surface of a polyester resin substrate produced by a coextrusion method or a lamination method.

[0129] The coating composition may be directly applied to the substrate surface, or may be applied via a primer layer, ultraviolet absorbing layer, printing layer, recording layer, infrared shielding layer, pressure-sensitive adhesive layer, inorganic deposited film layer, etc., as required.

[0130] The coating method can be appropriately selected and used from known coating methods such as a spin coater, notch wheel coater, lip coater, roll coater, die coater, knife coater, blade coater, rod coater, lick coater, gravure roll coater, screen coating, dip coating, and cast coating.

[0131] The thickness of the coating film prepared by the photocurable coating composition of the present invention is not particularly limited. Considering the prevention of coating film defects, exerting sufficient scratch resistance, and considering the prevention of crack generation, it is preferably 0.1 to 50 μm. In addition, considering the good performance of characteristics such as coating film hardness, scratch resistance, long-term stable adhesion and difficulty in cracking, it is more preferably 1 to 30 μm.

[0132] In addition, as required, other coating layers such as an adhesive layer, an ultraviolet absorbing layer, a printing layer, a recording layer, an infrared shielding layer, a pressure-sensitive adhesive layer, an inorganic vapor-deposited film layer, a water- and oil-proof layer, and a hydrophilic antifouling layer may be formed on the surface of the cured coating film of the photocurable coating composition of the present invention.

[0133] The cured coating film obtained from the photocurable coating composition of the present invention has excellent scratch resistance as described above. In order to obtain further scratch resistance, the present coating film may be coated with an inorganic vapor-deposited film layer.

[0134] As the inorganic vapor-deposited film layer, there is no particular limitation as long as it is an inorganic vapor-deposited film layer formed by a dry film-forming method, and examples thereof include layers mainly composed of various metals having at least one of elements such as Si, Ti, Zn, Al, Ga, In, Ce, Bi, Sb, B, Zr, Sn, and Ta, and oxides, nitrides, and sulfides of these metals. In addition, for example, a diamond-like carbon film layer having high hardness and excellent insulation properties can also be cited.

[0135] The stacking method of inorganic vapor-deposited film layers is not particularly limited as long as it is a dry film-forming method. For example, dry film-forming methods include physical vapor growth methods such as resistance heating evaporation, electron beam evaporation, molecular beam epitaxy, ion beam deposition, ion plating, sputtering, and chemical vapor growth methods such as thermal CVD, plasma CVD, photo CVD, epitaxial CVD, atomic layer CVD, catCVD, etc.

[0136] The coated article coated with the cured product of the coating composition of the present invention thus obtained can be an article having excellent scratch resistance and weather resistance, particularly excellent weather crack resistance.

[0137] The photocurable coating composition of the present invention is preferably used as a photocurable coating composition for articles used outdoors.

[0138] In particular, it is preferably used for the surface coating of automobile headlamp lenses, vehicle sensor covers, and resin glasses. The substrates of these are polycarbonates, which are usually well used because they have high impact resistance, heat resistance, transparency, and light weight. However, polycarbonates are not good enough in chemical resistance, weather resistance, scratch resistance, etc., so it is preferred to use the coating composition of the present invention to coat the surface to improve these properties.

[0139] In addition, the polycarbonate coated with the coating film composed of the photocurable coating composition of the present invention can prevent yellowing and weather cracking of the coating film, and also exhibits excellent water resistance and antifouling properties, is lightweight, and has easy formability. Therefore, it can be used in various applications such as automobile headlight lenses, vehicle sensors, vehicle windows, outdoor signs, window glass of greenhouses and outdoor buildings, roofs of balconies and garages, balconies, and instrument covers.

[0140] Example

[0141] The present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples.

[0142] In the following examples, "parts" and "%" mean "parts by mass" and "% by mass", respectively, unless otherwise specified. The apparatuses used in the examples are as follows.

[0143] (1) GPC measurement conditions

[0144] Equipment: HLC-8320GPC manufactured by Tosoh Corporation

[0145] Column: TSKgel G4000HXL+G3000HXL+G2000HXL+G2000HXL manufactured by Tosoh Corporation (each with an inner diameter of 6 mm and a length of 150 mm)

[0146] Elution solvent: tetrahydrofuran

[0147] Column tank temperature: 40°C

[0148] Flow rate: 1mL / min

[0149] Detector: Refractive Index (RI)

[0150] Standard: Monodisperse polystyrene

[0151] (2) Proton NMR spectroscopy ( 1 H-NMR) measurement conditions

[0152] Device: AVANCE III 400 manufactured by BRUKER

[0153] Solvent: CDCl3

[0154] Internal standard: tetramethylsilane (TMS)

[0155] (3) Infrared absorption spectrum (IR) measurement conditions

[0156] Apparatus: Nicolet 6700 manufactured by Thermo Fisher

[0157] [1] Synthesis of organopolysiloxane

[0158] [Synthesis example 1]

[0159] In a 500 mL brown glass reactor equipped with a stirrer, a thermometer, a reflux condenser and a dropping funnel, 96.7 g of dimethyl polysiloxane modified with carbinol at both ends (KF-6001 manufactured by Shin-Etsu Chemical Co., Ltd., hydroxyl value 58 mgKOH / g, following formula (13)), 48.4 g of butyl acetate, 0.03 g of tert-butylhydroxytoluene as a polymerization inhibitor, and 0.03 g of dioctyltin oxide as a urethanization catalyst were placed, and heated and stirred until the internal temperature reached 70°C. 50.2 g of 1,1-(bisacryloyloxymethyl)ethyl isocyanate (Karenz BEI manufactured by Showa Denko K.K., molecular weight 239) was added dropwise thereto over 1.5 hours while heating. Then, the mixture was reacted at 80°C for 3 hours, and 10 g of methanol was added to deactivate the residual isocyanate group, and the mixture was reacted at 70°C for 1 hour. After cooling to 25°C, IR was measured and the absorption peak from NCO (2260 cm -1 ) almost disappeared, confirming the consumption of Karenz BEI as a raw material. Next, the low molecular weight component was concentrated under reduced pressure and filtered through a nylon mesh (100 mesh) to obtain 156.8 g of light yellow transparent organopolysiloxane A-1. Its kinematic viscosity was 10400 mPa·s and the non-volatile component was 98.6%. In addition, the GPC, 29 The structure of A-1 confirmed by Si-NMR and IR measurements is shown in the following formula (14).

[0160] [Chemistry 15]

[0161]

[0162] [Chemistry 16]

[0163]

[0164] [Synthesis example 2]

[0165] In a 500 mL brown glass reactor equipped with a stirrer, a thermometer, a reflux condenser and a dropping funnel, 48.8 g of dimethyl polysiloxane modified with carbinol at both ends (KF-6000 manufactured by Shin-Etsu Chemical Co., Ltd., hydroxyl value 115 mgKOH / g, following formula (15)), 48.8 g of butyl acetate, 0.03 g of t-butylhydroxytoluene as a polymerization inhibitor, and 0.03 g of dioctyltin oxide as a urethanization catalyst were placed, and heated and stirred until the internal temperature reached 60° C. Then, 22.2 g of isophorone diisocyanate (Desmodur I manufactured by COVESTRO, molecular weight 222) was added dropwise thereto over 1 hour while heating. Then, the mixture was reacted at 60°C for 3 hours, 80.7 g of a mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate (made by MIWON, MIRAMER M340, mixing ratio 57% / 43%, hydroxyl value 139 mgKOH / g) was added, the temperature was raised to 80°C, and the mixture was stirred for 3 hours. In order to deactivate the residual isocyanate groups, 10 g of methanol was added, and the mixture was reacted at 80°C for 1 hour. After cooling to 25°C, the low molecular weight components were concentrated under reduced pressure and filtered through a nylon mesh (100 mesh) to obtain 147.6 g of light yellow transparent organopolysiloxane A-2. The kinematic viscosity at 40°C was 37100 mPa·s, and the non-volatile component was 97.5%. In addition, the GPC, 1 The structure of A-2 confirmed by H-NMR and IR measurements is shown in the following formula (16).

[0166] [Chemistry 17]

[0167]

[0168] [Chemistry 18]

[0169]

[0170] [Synthesis example 3]

[0171] In a 1 L brown glass reactor equipped with a stirrer, a thermometer, a reflux condenser and a dropping funnel, 155.8 g of dimethyl polysiloxane modified with carbinol at both ends (KF-6002 manufactured by Shin-Etsu Chemical Co., Ltd., hydroxyl value 36 mgKOH / g, following formula (17)), 155.8 g of butyl acetate, 0.05 g of tert-butylhydroxytoluene as a polymerization inhibitor, and 0.05 g of dioctyltin oxide as a urethanization catalyst were placed, and heated and stirred until the internal temperature reached 60° C. 22.2 g of isophorone diisocyanate (Desmodur I manufactured by COVESTRO, molecular weight 222) was added dropwise thereto over 1 hour while heating. Then, the mixture was reacted at 60°C for 3 hours, 224.4 g of a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (A-9550, manufactured by Shin-Nakamura Chemical Industry Co., Ltd., hydroxyl value 50 mgKOH / g) was added, the temperature was raised to 80°C, and the mixture was stirred for 3 hours. In order to deactivate the residual isocyanate groups, 10 g of methanol was added, and the mixture was reacted at 80°C for 1 hour. After cooling to 25°C, the low molecular weight components were concentrated under reduced pressure and filtered through a nylon mesh (100 mesh) to obtain 379.6 g of light yellow transparent organopolysiloxane A-3. The kinematic viscosity at 40°C was 68400 mPa·s, and the non-volatile component was 98.2%. In addition, the GPC, 1 The structure of A-3 confirmed by H-NMR and IR measurements is shown in the following formula (18).

[0172] [Chemistry 19]

[0173]

[0174] [Chemistry 20]

[0175]

[0176] [Comparative Synthesis Example 1]

[0177] In a 500 mL brown glass reactor equipped with a stirrer, a thermometer, a reflux condenser and a dropping funnel, 48.8 g of dimethyl polysiloxane modified with carbinol at both ends (KF-6000 manufactured by Shin-Etsu Chemical Co., Ltd., hydroxyl value 115 mgKOH / g, the above formula (15)), 48.8 g of butyl acetate, 0.03 g of tert-butylhydroxytoluene as a polymerization inhibitor, and 0.03 g of dioctyltin oxide as a urethanization catalyst were placed, and heated and stirred until the internal temperature reached 60°C. While heating, 22.2 g of isophorone diisocyanate (Desmodur I manufactured by COVESTRO, molecular weight 222) was added dropwise over 1 hour. Then, the mixture was reacted at 60°C for 3 hours, and 23.2 g of 2-hydroxyethyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd., molecular weight 116) was added, and the temperature was raised to 80°C and stirred for 3 hours. In order to deactivate the residual isocyanate groups, 10 g of methanol was added and the mixture was reacted at 80°C for 1 hour. After cooling to 25°C, the low molecular weight components were concentrated under reduced pressure and filtered through a nylon mesh (100 mesh) to obtain 90.8 g of light yellow transparent polysiloxane A-4. Its kinematic viscosity was 820 mPa·s and the non-volatile content was 98.1%. In addition, the GPC, 1 The structure of A'-4 confirmed by H-NMR and IR measurements is shown in the following formula (19).

[0178] [Chemistry 21]

[0179]

[0180] [Synthesis Example 4] Synthesis of Organopolysiloxane D-1 Having a (Meth) Acryloyl Group but Not Having a Urethane Bond

[0181] 142 g of acryloxypropyltrimethoxysilane (KBM5103 manufactured by Shin-Etsu Chemical Co., Ltd.), 500 g of isopropyl alcohol, 0.1 g of p-methoxyphenol, 1.0 g of tetramethylammonium hydroxide, and 20 g of deionized water were mixed and reacted at 20° C. for 24 hours to obtain a colorless transparent liquid. The mixture was concentrated by distillation under reduced pressure to obtain a colorless transparent liquid organopolysiloxane D-1.

[0182] [Synthesis example 5]

[0183] A mixed solution of 2.8 g of acryloxypropyltrimethoxysilane (KBM5103 manufactured by Shin-Etsu Chemical Co., Ltd.), 95.6 g of methyl ethyl ketone dispersed silica sol (MEK-ST manufactured by Nissan Chemical Co., Ltd., number average particle size 45 nm, silica concentration 30%), and 0.1 g of ion exchange water was stirred at 80° C. for 3 hours, and then 1.4 g of trimethyl orthoformate was added, and the mixture was heated and stirred at the same temperature for 1 hour to obtain a dispersion of surface-treated silica particles D-3. The solid content of the obtained dispersion was 32% by mass, and the average particle size of the surface-treated silica particles D-3 was 45 nm.

[0184] [2] Preparation of coating composition and production of coated articles

[0185] [Examples 1-1 to 1-8, Comparative Examples 1-1 to 1-5]

[0186] The following components (A) to (F) were stirred and mixed at 25° C. in the amounts shown in Tables 1 and 2, and then filtered through filter paper to prepare coating compositions (X1 to X8).

[0187] (A)Ingredients

[0188] A-1: Organopolysiloxane obtained in Synthesis Example 1

[0189] A-2: Organopolysiloxane obtained in Synthesis Example 2

[0190] A-3: Organopolysiloxane obtained in Synthesis Example 3

[0191] A'-4 (comparative component): organopolysiloxane obtained in comparative synthesis example 1

[0192] (B) Ingredients

[0193] B-1: 2-[4-[(2-hydroxy-3-(2'-ethyl)hexyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine (produced by BASF, Tinuvin 405)

[0194] B-2: A compound represented by the following structural formula (20) obtained by the method described in Synthesis Example 1 of Japanese Patent No. 6354665.

[0195] [Chemistry 22]

[0196]

[0197] (C) Ingredients

[0198] C-1: 2,4,6-trimethylbenzoyldiphenylphosphine oxide (manufactured by BASF)

[0199] C-2: 1-Hydroxycyclohexyl phenyl ketone (manufactured by BASF, Irgacure 184)

[0200] (D) Ingredients

[0201] D-1: Acryloyl-containing organopolysiloxane obtained in Synthesis Example 4

[0202] D-2: Acryloyl group-containing organopolysiloxane (manufactured by Shin-Etsu Chemical Co., Ltd., KR-513)

[0203] D-3: Surface treated silica particles obtained in Synthesis Example 5 (32 mass % methyl ethyl ketone dispersion)

[0204] (E) Ingredients

[0205] E-1: Dipentaerythritol hexaacrylate (Made by MIWON, MIRAMER M600)

[0206] E-2: 1,6-Hexanediol diacrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., A-HD-N)

[0207] (F) Additives

[0208] F-1: Polyether silicone leveling agent (manufactured by Shin-Etsu Chemical Co., Ltd., leveling agent A)

[0209] F-2: an acrylate compound having a perfluoropolyether group represented by the following formula (21), obtained by the method described in Example 1 of Japanese Patent No. 4873666

[0210] [Chemistry 23]

[0211]

[0212] Rf: -CF2(OCF2CF2) p (OCF2) q OCF2-(p / q=0.9、p+q≒45)

[0213] F-3: an organopolysiloxane represented by the following formula (22) obtained by the method described in Synthesis Example 1 of International Publication No. WO2022 / 065019

[0214] [Chemistry 24]

[0215]

[0216] (In the formula, Me represents a methyl group, and Bu represents an n-butyl group.)

[0217] (G) Solvent

[0218] G-1: Propylene glycol monomethyl ether (PGM)

[0219] [Table 1]

[0220]

[0221] [Table 2]

[0222]

[0223] [Examples 2-1 to 2-8, Comparative Examples 2-1 to 2-5]

[0224] The coating compositions obtained in the above-mentioned examples and comparative examples were applied to the surface of a polycarbonate NF-2000 sheet (2 mm thick × 15 cm long × 10 cm wide) manufactured by Mitsubishi Engineering-Plastics Co., Ltd. by flow coating, and then air-dried for 5 minutes. The sheets were then heated at 80°C for 1 minute and then heated at 600 mJ / cm using a high-pressure mercury lamp. 2 The coating film was cured by irradiating with light at an irradiation amount of , and the following evaluations were performed on the obtained test pieces. The results are shown in Tables 3 and 4.

[0225] (1) Coating appearance

[0226] The coating film was visually observed to determine whether there was any abnormality.

[0227] ○: No abnormality

[0228] △: Colored

[0229] ×: There are abnormalities such as foreign matter, unevenness, cracks, or peeling.

[0230] (2) Haze

[0231] The haze of the coated sheet was measured using a haze meter NDH5000SP manufactured by Nippon Denshoku Industries Co., Ltd.

[0232] (3) SW resistance

[0233] The haze was measured after 11 reciprocating cycles with a load of 500 g using a Gakushin abrasion tester AB-301 manufactured by Tester Industry Co., Ltd. and steel wool No. 0000. The difference in haze between before and after the test was defined as scratch resistance. If the difference in haze was 7 or less, the test was considered acceptable.

[0234] (4) Water contact angle

[0235] A 2 μL droplet of pure water was brought into contact with the coating film using a fully automatic contact angle meter DM-701 manufactured by Kyowa Interface Science Co., Ltd., and the contact angle at that time was measured. A contact angle of 95° or more was considered acceptable.

[0236] (5) Erasability with a marker

[0237] A line of about 2 cm was drawn on the coating film using HI McKee (registered trademark) black manufactured by Zebra Co., Ltd., and then rubbed twice with Kaydry (registered trademark) manufactured by Nippon Paper Crecia Co., Ltd. The appearance was visually observed and judged according to the following criteria.

[0238] ○: No residual traces, wipe cleanly

[0239] △: Mostly erased, but traces can be confirmed

[0240] ×: Almost no erasure

[0241] (6) Weather resistance evaluation

[0242] The EYE SUPER UV TESTER W-151 manufactured by Iwasaki Electric Co., Ltd. was used to test the black panel at a temperature of 63°C, a humidity of 50% RH, and an illumination of 50 mW / cm 2 The test was conducted for 300 hours under the condition of repeating the cycle of [black panel temperature 30°C, humidity 95% RH, 1 hour] as one cycle. The coating film after the weather resistance test was evaluated for its appearance, haze, water contact angle, and erasability with a marker.

[0243] [Table 3]

[0244]

[0245] [Table 4]

[0246]

[0247] The coatings obtained from the coating compositions (X1 to X8) of Examples 1-1 to 1-8 had a water contact angle of 95° or more after the weathering test, and excellent erasability with a marker. In particular, the coatings of Examples 1-2 to 1-8 (X2 to X8) using ultraviolet absorbers having an acryloyl group did not discolor after the weathering test, and had a more excellent appearance. This result is presumed to be due to the suppression of precipitation of the ultraviolet absorber.

[0248] On the other hand, the coatings composed of the compositions of Comparative Example 1-1 (R1) not containing the organopolysiloxane of the component (A) and Comparative Examples 1-4 and 1-5 (R4, R5) in which the content of the component (A) is less than 30% by mass in terms of non-volatile matter in the composition have poor water contact angles and erasability with a marker, and cracks were found in the coatings after the weather resistance test (R1, R4).

[0249] The coating film formed of the composition of Comparative Example 2-1 (R2) in which the organopolysiloxane of component (A) was changed to an organopolysiloxane having a=1 had uneven coating appearance and poor abrasion resistance. In addition, the water contact angle after the weather resistance test and the erasability with a marker were reduced.

[0250] The coating film composed of the composition of Comparative Example 3 (R3) which did not contain the ultraviolet absorber as the component (B) turned yellow after the weather resistance test and also partially peeled off.

Claims

1. A photocurable coating composition comprising: (A) an organopolysiloxane represented by the following formula (1), [Chemistry 1] In the formula, R 1 independently represent a hydrogen atom or a monovalent hydrocarbon group which may have an oxygen atom interposed therein, X independently represents a divalent saturated hydrocarbon group which may contain one or more atoms selected from oxygen, nitrogen, sulfur and phosphorus atoms, Q independently represents a (a+1)-valent saturated hydrocarbon group which may contain one or more atoms selected from oxygen, nitrogen, sulfur, phosphorus and silicon atoms, P independently represents an acryloyloxy group or a methacryloyloxy group, a independently represents an integer from 2 to 5, n represents an integer from 0 to 100, (B) an ultraviolet absorber, and (C) a photopolymerization initiator, The content of the component (A) calculated as a non-volatile matter is 30 to 99% by mass.

2. The photocurable coating composition according to claim 1, wherein The R 1 It is methyl.

3. The photocurable coating composition according to claim 1, wherein The X's are independently a divalent saturated hydrocarbon group having 2 to 30 carbon atoms which may have an oxygen atom interposed therein.

4. The photocurable coating composition according to claim 3, wherein The X is a group represented by the following formula (2), [Chemistry 2] In the formula, *1 is bonded to the silicon atom of the formula (1), and *2 is bonded to the oxygen atom in the urethane group of the formula (1).

5. The photocurable coating composition according to claim 1, wherein The Q's are each independently a saturated hydrocarbon group having 4 to 30 carbon atoms and having a urethane bond and having a valence of (a+1).

6. The photocurable coating composition according to claim 1, wherein The n is an integer of 1-80.

7. The photocurable coating composition according to claim 1, wherein The component (B) is a UV absorber having a (meth)acryloyl group.

8. The photocurable coating composition according to claim 1, comprising (D) one or more selected from an organopolysiloxane having a (meth)acryloyl group but not having a urethane bond, and silica particles surface-modified with an alkoxysilane having a (meth)acryloyl group but not having a urethane bond. 9 . The photocurable coating composition according to claim 1 , comprising (E) a (meth)acrylate compound having no silicon atom, wherein the component (E) does not include the component (B). 10 . A cured film of the photocurable coating composition according to claim 1 .

11. A covered article, comprising: A substrate, and a cured film of the photocurable coating composition according to claim 10 formed on the substrate directly or via at least one other layer.

12. The coated article according to claim 11, wherein The substrate is organic resin or wood.

Citation Information

Patent Citations

  • JP1973073666A

  • JP1974010253A

  • Sampler for lower part of shaft of blast furnace

    JP1986056214A

  • Automatic changing processing machine for reservation ticket

    JP1988054665A

  • Glow plug

    JP1990110212A